Perlindungan hukum bagi pencipta ari bias atas lagu yang dinyanyikan ulang oleh agnez mo di superclub berdasarkan undang-undang nomor 28 tahun 2014 - Shafira Fajriah Arrozi; Anne Gunawati; Rully Syahrul Mucharom (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2026)
Copyright protection is a legal mechanism that safeguards creators' exclusive and economic rights over their intellectual works. The dispute between Ari Bias and Agnez Mo regarding the commercial performance of the song Bilang Saja generated significant legal debate after the Supreme Court, through Decision Number 825 K/Pdt.Sus-HKI/2025, overturned the Commercial Court Decision Number 92/Pdt.Sus-HKI/2024/PN Niaga Jkt.Pst. This study aims to examine the conformity of the Supreme Court's decision with Law Number 28 of 2014 on Copyright and to analyze the legal consequences arising from the differing judicial interpretations. The research employed a normative-empirical method using statutory and case approaches, supported by interviews with the songwriter, the National Collective Management Organization, and the Directorate General of Intellectual Property. Primary and secondary data were analyzed qualitatively. The findings indicate that the Supreme Court's decision is only partially consistent with the Copyright Law because it emphasizes royalty payment obligations while providing insufficient protection for the creator's exclusive right to authorize the commercial use of copyrighted works. The conflicting judicial decisions also create legal uncertainty regarding the party responsible for obtaining permission and paying royalties for commercial performances. Therefore, harmonization of legal interpretation and strengthening of regulations governing licensing and royalty mechanisms are essential to ensure legal certainty, effective copyright protection, and justice for song creators in Indonesia.